Improving heat transfer coefficient during double-sided meat frying - Skrypnyk, Vyacheslav; Bychkov, Yaroslav; Molchanova, Natalyia; Farisieiev, Andrii (Eastern-European Journal of Enterprise Technologies, 2017)
Improving the energy efficiency of technological processes and equipment for heat treatment of meat and meat products is a relevant scientific task. A prerequisite for the development of new energy and resource-saving equipment for frying meat is the study of the mechanism of heat transfer in the surface layers of the product. The aim of the work was to determine the effect of the value of the logarithmic mean temperature difference (LMTD) on the value of the heat transfer coefficient k during ouble-sided frying of organic meat products by the physical and electrophysical methods. The study has proved that the LMTD between the frying surface temperature and the temperature of liquid on the capillary meniscus surface depend on the frying surface temperature. An increase in the frying surface temperature from 393 K to 423 K reduces the LMTD between the frying surface temperature and the temperature of liquid on the meniscus surface from 10 K to 6 K. The specified method of calculating the coefficient of heat transfer through vapor layers takes into account the change in the contact area of the meniscus liquid with the frying surface during evaporation and the area of the meniscus surface in the vapor condensation during double-sided frying of pork under pressure. The study has proved the dependence of the heat transfer coefficient on the LMTD between the temperature of the frying surface and the temperature of liquid on the meniscus surface. The calculated actual coefficient of heat transfer from the frying surface to the product is k423=3800 W/(m2 K) for the LMTD =10 K and k393=3800 W/(m2 K) at K. The theoretically substantiated duration of double-sided frying of organic meat under compression is completely identical to the real one.